AGRICULTURAL INPUT MARKET IN ROMANIA WITHIN THE CONTEXT OF THE WORLDWIDE CRISIS - Tudor, Roxana (Economics of Agriculture, 2012)
Within the double context of the worldwide crisis and the crisis of the Romanian economy, of the factors that contribute to the achievement of performance within the economic system an important role, as far as ensuring an increased level of productivity is concerned, is played by the agricultural inputs. The analysis carried out upon the market of agricultural inputs in Romania underline a decrease of performance of the domestic input producers in front of an increased external competitiveness, which also has a strong impact upon the food industry